A Partial Theory of Takeover Bids - ASHTON, D. J.; ATKINS, D. R. (Journal of Finance, 1984)
ABSTRACT There is a natural separation between production decisions affecting the firm as a whole and individual decisions by each shareholder about his portfolio of securities. The end result of these two types of decisions is normally referred to as a productive exchange equilibrium. At such an equilibrium, no individual wants to adjust his portfolio and no firm can muster majority support for a change in its production plans. This paper presents a partial theory of takeover bids in that it examines the role of a takeover bid as a mechanism by which a simultaneous change in shareholdings and production plans can be achieved. This enables a new production exchange equilibrium to be reached which is preferred by a majority of the shareholders but which is inaccessible without a contingent contract in the form of a takeover bid.